Individual characteristics as correlates of library personnel’s attitüde towards preservation of information resources in Nigerian federal university libraries (2009)
This study investigated the effect of individual characteristics of personnel like gender, age, educational qualification, work experience, on attitude towards preservation of information resources in federal university libraries in Nigeria. The research data was collected through questionnaire method from 660 library personnel consisting of Professional and para- professional library staff randomly sampled, out of which 510 responded. The study found that gender was not significantly related to attitude towards preservation of information resources but a significant relationship was found to exist between educational qualification and attitude. It was also established that age and sections of work of the personnel were not correlated with their attitude towards preservation of information resources. Some necessary suggestions based on the findings were made.